Diagnostic value of BI-RADS categories in the management of patients with benign breast pathology - G. P. Korzhenkova (ABV-press, 2017)
Reasonable tactics of management of the patients with breast disease depends of the quality of diagnostics methods. Modern requirements to the methods of diagnosis - a precision, high information value, accessibility. In the article BI-RADS (Breast Imaging Reporting and Data System) is being discussed. This system is a good tool to determine the proper algorithm of breast disease patients' management.